2018
DOI: 10.1371/journal.pone.0190080
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, breed composition and admixture of Kenyan domestic pigs

Abstract: The genetic diversity of African pigs, whether domestic or wild has not been widely studied and there is very limited published information available. Available data suggests that African domestic pigs originate from different domestication centers as opposed to international commercial breeds. We evaluated two domestic pig populations in Western Kenya, in order to characterize the genetic diversity, breed composition and admixture of the pigs in an area known to be endemic for African swine fever (ASF). One o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 18 publications
1
44
1
Order By: Relevance
“…Among the European commercial breeds Duroc, Landrace, and Yorkshire, two AHR gene copies were detected in 46.1, 67.0, and 66.9%, respectively, of the tested population. Previous studies indicated the Landrace and Large White were much more closely related than Duroc at the genome-wide level [54,55], thus the higher proportion in Landrace and Yorkshire compared to Duroc could be attributed to the differences in the genome level among the three breeds. Landrace and Yorkshire were commonly used as maternal pigs, which are selected in the artificial breeding process based on large litter size.…”
Section: The Copy Number Of Ahr Gene Is Associated With Pig's Litter mentioning
confidence: 98%
“…Among the European commercial breeds Duroc, Landrace, and Yorkshire, two AHR gene copies were detected in 46.1, 67.0, and 66.9%, respectively, of the tested population. Previous studies indicated the Landrace and Large White were much more closely related than Duroc at the genome-wide level [54,55], thus the higher proportion in Landrace and Yorkshire compared to Duroc could be attributed to the differences in the genome level among the three breeds. Landrace and Yorkshire were commonly used as maternal pigs, which are selected in the artificial breeding process based on large litter size.…”
Section: The Copy Number Of Ahr Gene Is Associated With Pig's Litter mentioning
confidence: 98%
“…It is possible that a resource worth further investigation exists in the ECSA countries in the form of pig populations that have demonstrated a natural resistance to virulent ASF viruses. Greater resistance to the pathogenic effects of ASF virus in some populations of traditionally kept pigs has been investigated in Mozambique, Kenya and Uganda (Muhangi et al, ; Mujibi et al, ; Okoth et al, ; Penrith et al, ) and evidence for resistance based on healthy pigs with antibodies to ASF or lower than expected mortality has been reported in Angola, Malawi, Mozambique, Tanzania and Uganda (Allaway, Chinombo, Edelsten, Hutchings, & Sumption, ; Atuhaire, Afayoa, Ochwo, Mwesigwa, Mwiine, et al, ; Atuhaire et al, ; Haresnape, Lungu, & Mamu, , ; Nsalambi, ; Penrith et al, ; Uttenthal et al, ). Obtaining and managing wild African suids for experimental studies is challenging, but genetic and immunological studies on domestic pigs from populations with demonstrated resistance could provide vital information for vaccine development.…”
Section: Knowledge Gaps and The Way Forwardmentioning
confidence: 99%
“…Sufficient genetic variation was, however, estimated for pig populations in Ghana and South Africa that can support genetic improvement for many growth and carcass traits in the breed [10,13]. Mujibi et al (2018) [14] observed a significant introgression of genes from international commercial breeds into the Busia pigs in Kenya. Following various periods of utilization in South Africa, molecular data describing levels of diversity in these breeds are not available.…”
Section: Origins and Description Of Domestic Free-range Pigs In Southmentioning
confidence: 99%
“…The domestic free-range pigs in Southern Africa have a slower growth rate than exotics, their major strength being adaptive traits that give them an advantage in low-intensity management smallholder systems [9]. Invariably, the genetic heritage of domestic free-range pigs is constantly threatened by genetic erosion caused by some indiscriminate crossbreeding with exotic breeds [14]. There are a few pig genetic and phenotypic characterization studies.…”
Section: Origins and Description Of Domestic Free-range Pigs In Southmentioning
confidence: 99%